PENGARUH KARAKTERISTIK PERUSAHAAN, KINERJA PERUSAHAAN, DAN MANAGEMENT ENTRENCHMENT TERHADAP MANAJEMEN LABA - Tang, Sukiantono; Fiorentina, Fiorentina (Fakultas Ekonomi dan Bisnis, UNTAN, 2021)
ABSTRACTThe purposes of this study is to investigate the impact of firm characteristics, firm performances, and management entrenchment on earnings management by using firms registered on Bursa Efek Indonesia for the period 2015-2019. Sampling method that is used in this study is purposive sampling method so the objects should meet the criteria. The exception sample for this study is financial firms due to differences on some regulations of reporting and firms without complete annual and financial report published for the period 2015-2019. The secondary data were obtained from firms